Perancangan Pop Up Book tentang Perjuangan Pejuang Perempuan Siti Manggopoh - Vernanda Em Afdhal; Hadrila Putri Aswara (fakultas Desain Koomunikasi visual, 2021)
This study, entitled Designing a Pop Up Book about the Struggle of the Women's Warrior Siti Manggopoh, discusses the history of a woman's heroism in leading the struggle against Dutch colonialism, which at that time implemented a money tax policy (belasting). The uprising occurred on June 15, 1908. The Manggopoh People's Struggle Movement led by Siti Manggopoh was able to influence other people so that they joined forces against the Dutch and the Manggopoh War broke out which the Dutch East Indies government could not forget. The history of the nation will be lost if it is not preserved. It takes various forms of effort and media design to introduce the history of the female warrior Siti Manggopoh to the people of West Sumatra in particular and Indonesia in general. The author wants to design an effective media in the form of a Pop Up Book, so that the younger generation is now interested in history which at this time is only focused on text books. The data used in this design are verbal data, visual data and data obtained through interviews, observations, and documentation which were analyzed by SWOT analysis.